(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the linguistic-cultural and pragmalinguistic representation of the concept agreement in Charlotte Brontë’s Jane Eyre. Using a corpus-based qualitative method, the research explores how agreement functions as a culturally embedded communicative act shaped by Victorian moral values, social hierarchy, gender norms, and religious ideology. Findings reveal four major semantic domains—moral responsibility, social hierarchy, female agency, and religious obedience—and five pragmatic strategies: directive softening, face-saving, moral positioning, power negotiation, and boundary management. Agreement in the novel appears not as a simple act of acceptance but as a complex negotiation between personal autonomy and societal expectations. This study contributes to literary pragmatics and cultural linguistics by offering a systematic analysis of how interpersonal alignment is linguistically constructed in Victorian fiction.